Revisiting Jamuna bridge resettlement areas: exploring livelihood status of the affected people - Ghosh, Shyamal C; Rahman, Hasanur; Rana, AKM Masud (BRAC, 2019)
Jamuna Multipurpose Bridge (JMB) project was the first of its kind which incorporated resettlement activities facilitating livelihood restoration of the project affected people (PAP). This study was an endeavor to reveal the livelihood status of the PAP after the implementation of the project in 1998, using both quantitative and qualitative methods. Findings revealed that though the livelihood of the PAP were affected due of loss of land or other assets and/or change of occupation, failure to utilize the compensation money, unavailability of skill development training they could manage to restore their livelihood during the post-project time. Regardless of the category of PAP, the rates of literacy (59%) as well as the use of tube well water (99%), sanitary latrine (40%), and electricity (50%) increased in both districts during the post-project time from that of pre-project time. Additionally, the status of child immunization (86% in Tangail and 91% in Sirajganj) and the use of contraceptive (61% in Tangail and 67% in Sirajganj) was also higher than the national status after the bridge construction. Self-rated food security status showed the reduced proportion of deficit households i.e. from 64% during the pre-project time to 55% during post-project time. All these factors indicated the improvement of quality of life during the postproject time. However, the PAP faced difficulty since agriculture was severely affected due to land acquisition and people shifted to non-farm activities. The logistic regression indicated that the probability of reporting good quality of life was less likely among the poor, who owned less than 50 decimals of land as well as the PAP who were in Sirajganj compared to their counterparts. The JMB resettlement policy and activities were not always appreciated by the PAP and thus, a future resettlement activity for any similar project needs revision to make it more effective for livelihood restoration with minimum difficulties.